2009
DOI: 10.1377/hlthaff.28.5.w957
|View full text |Cite
|
Sign up to set email alerts
|

A Trade Agreement's Impact On Access To Generic Drugs

Abstract: Millions of people lack access to affordable medicines. The intellectual property rules in the Central America Free Trade Agreement (CAFTA) provide pharmaceutical companies with monopoly protections that allow them to market some drugs without competition by less costly generics. We examined availability of certain drugs in Guatemala and found that CAFTA intellectual property rules reduced access to some generic drugs already on the market and delayed new entry of other generics. Some drugs protected from comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 2 publications
1
35
0
Order By: Relevance
“…A 2012 joint report from the WTO, the WHO, and the World Intellectual Property Organization describes the impact of TRIPS-Plus provisions-particularly data exclusivity provisionsdictated by trade agreements in Costa Rica, the Dominican Republic, Colombia, and Jordan, as increasing the expenditure on medicines by tens of millions of dollars (149) (119). The extension of IP protections in FTAs acts as a barrier to the generic pharmaceutical industry's ability to manufacture and distribute cheaper medicines sooner and, thus, acts as a barrier to affordable, timely access to medicine (86).…”
Section: Health Servicesmentioning
confidence: 99%
“…A 2012 joint report from the WTO, the WHO, and the World Intellectual Property Organization describes the impact of TRIPS-Plus provisions-particularly data exclusivity provisionsdictated by trade agreements in Costa Rica, the Dominican Republic, Colombia, and Jordan, as increasing the expenditure on medicines by tens of millions of dollars (149) (119). The extension of IP protections in FTAs acts as a barrier to the generic pharmaceutical industry's ability to manufacture and distribute cheaper medicines sooner and, thus, acts as a barrier to affordable, timely access to medicine (86).…”
Section: Health Servicesmentioning
confidence: 99%
“…A recent study showed that the implementation of a data exclusivity regime in Guatemala, mandated by DR-CAFTA, resulted in generic competition being denied entry to the Guatemalan market. 72 In each case, the available originator drugs were priced substantially higher. 73 Especially in those countries which, pre-TRIPS, did not grant patents for pharmaceuticals, data exclusivity can be an efficient method to ensure market exclusivity for originator drugs and prevent generic competition in that market.…”
Section: Data Exclusivity and (Affordable) Access To Medicines In Devmentioning
confidence: 99%
“…In Jordan, the application of data exclusivity increased medicine price by 20% from 2001 to 2009 (Shaffer & Brenner, 2009). For cancer and cardiovascular medicines, in particular, prices increased by 2-10 times.…”
Section: The Impact Of Increased Medicine Pricesmentioning
confidence: 99%
“…Studies of the impacts of similar trade agreements, such as the Central America Free Trade Agreement (CAFTA) and other bilateral agreements between the USA and developing countries, revealed that these agreements reduced access to some generic drugs already on the market and delayed the entry of other new generics (Rohit, 2007;Shaffer & Brenner, 2009). During the early 2000s, generic competition led to a precipitous price reduction in antiretroviral therapy (ART) from over USD 10,000 per person per year (ppy) in 2000 to under USD 75 ppy by 2011 (El Said & Kapczynski, 2011).…”
Section: Introductionmentioning
confidence: 99%